18S Analysis of the Taxonomic Position of an Endoparasitic Pycnogonid, Nymphonella Tapetis (Arthropoda: Pycnogonida: Ascorhynchidae). Issue 4 (1st July 2015) - Miyazaki, Katsumi; Tomiyama, Takeshi; Yamada, Katsumasa; Tamaoki, Masanori
Abstract: We obtained the nucleotide sequence of 18S rDNA of Nymphonella tapetis, a pycnogonid endoparasitic on some bivalves, together with that of other species belonging to Ascorhynchidae Hoek, 1881 . The phylogenetic tree based on these sequences as well as those of selected species from a database strongly supports the monophyly of Ascorhynchidae and the inclusion of Nymphonella in the family. Nymphonella seems to be an aberrant form in the Ascorhynchidae, but multi-gene analysis with more species is required for the exact determination of the taxonomic position of the genus.